Arrestin-Coding Genes Regulate Endocytosis, Sporulation, Pathogenicity, and Stress Resistance in Arthrobotrys oligospora - Zhou, Liang; Li, Mengfei; Cui, Peijie; Tian, Mengqing; Xu, Ya; Zheng, Xi; Zhang, Keqin; Li, Guohong; Wang, Xin (Frontiers in Cellular and Infection Microbiology, 2022)
Arrestins are a family of scaffold proteins that play a crucial role in regulating numerous cellular processes, such as GPCR signaling. The Arthrobotrys oligospora arrestin family contains 12 members, which have highly conserved N-terminal and C-terminal domains. In the presence of ammonia, A. oligospora can change its lifestyle from saprotrophic to carnivorous. During this transition, the expression pattern of arrestin-coding (AoArc) genes was markedly upregulated. Therefore, we disrupted 7 AoArc genes from A. oligospora for identifying their functions. Although individual arrestin mutant strains display similar pathogenesis, phenotypes, and stress resistance, the fundamental data on the roles of AoArc genes in A. oligospora are obtained in this study. Membrane endocytosis in AoArc mutants was significantly reduced. Meanwhile, the capacity of trap device formation against nematodes and ammonia was impaired due to the AoArc deletions. We also found that AoArc genes could regulate conidial phenotypes, cell nuclear distribution, pH response, and stress resistance. qRT-PCR assays revealed that the sporulation-regulated genes were affected after the deletion of AoArc genes. In particular, among the 12 arrestins, AoArc2 mediates pH signaling in the fungus A. oligospora. Notably, combined with the classical paradigm of arrestin-GPCR signal transduction, we suggest that arrestin-regulated trap formation in A. oligospora may be directly linked to the receptor endocytosis pathway.